Ink composition and its use

The ink composition, featuring composite silver nanoparticles, polyvinyl acetal resin, and solvent, addresses the balance between metallic gloss and adhesion/abrasion resistance in existing technologies, achieving superior performance without additional layers.

JP7655880B2Active Publication Date: 2025-04-02MITSUBOSHI BELTING LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022039806
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-16
Filing Date
2022-03-15
Publication Date
2025-04-02
Estimated Expiration
2042-03-15

AI Technical Summary

Technical Problem

Existing ink compositions using metal nanoparticles struggle to achieve a balance between metallic gloss, adhesion, and abrasion resistance, often requiring a trade-off between these characteristics and necessitating the use of topcoat and undercoat layers.

Method used

The development of an ink composition that combines composite nanoparticles of silver with a protective colloid, a polyvinyl acetal resin, and a solvent, allowing for improved metallic gloss and maintaining adhesion and abrasion resistance without the need for additional layers.

Benefits of technology

The ink composition achieves high metallic gloss, excellent adhesion, and enhanced abrasion resistance, while also providing a dense layer of silver-containing nanoparticles for improved light shielding and mirror surface appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655880000007
    Figure 0007655880000007
  • Figure 0007655880000008
    Figure 0007655880000008
  • Figure 0007655880000009
    Figure 0007655880000009
Patent Text Reader

Abstract

To provide an ink composition which is excellent in metallic glossiness.SOLUTION: An ink composition contains composite nanoparticles (A) of metal containing silver and a protective colloid, a resin composition (B) containing a polyvinyl acetal-based resin and a solvent (C). The polyvinyl acetal-based resin may be a polyvinyl butyral-based resin. The resin component (B) may further contain a second resin. The second resin may be at least one selected from the group consisting of a (meth)acrylic resin, an alkyd resin, an epoxy resin and a cellulose-based resin. The solvent (C) may contain at least one selected from the group consisting of esters, alkylene glycol monoalkyl ether and dialkylene glycol monoalkyl ether.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metallic luster ink composition for metallically decorating various objects to be decorated, and uses thereof. [Background technology]

[0002] Metallic decoration is required in a wide range of fields, such as interior and exterior parts of automobiles, emblems, electronic devices, cosmetic containers, golf club shafts, etc., and a high level of metallic luster comparable to that of metal is required to achieve a sense of luxury. In particular, silver has a high light reflectance and therefore a beautiful metallic luster (metallicity, brilliance, mirror-like quality), and is expected to be a metal suitable for advanced design.

[0003] Methods for imparting a metallic luster to a decorated object include foil stamping, vapor deposition, silver mirror plating using the silver mirror reaction, chrome plating, as well as methods for forming a metallic luster layer on a substrate by printing or coating with an ink that uses an aluminum pigment as a luster pigment or an ink that contains metal nanoparticles.

[0004] Foil stamping, vapor deposition, silver mirror plating, and chrome plating can impart a metallic luster close to that of metal, but the manufacturing process is complicated and specialized equipment is required, making them disadvantageous in terms of manufacturing costs. Silver mirror plating also suffers from the problems of whitening, cracks, and uneven coloring that are unique to plating, and has a high defect rate due to areas not intended for plating being plated. Furthermore, chrome plating places a heavy burden on the environment. In contrast to these methods, methods such as printing and coating using ink are inexpensive to manufacture and can be applied to a wide range of substrates.

[0005] Among inks, a metallic luster layer made from ink containing metal nanoparticles has superior metallic luster to ink using aluminum pigments (lustrous pigments).

[0006] JP 2009-227736 A (Patent Document 1) describes an ink composition for inkjet printing, which contains metal colloid particles formed of metal nanoparticles and a dispersant; and a solvent (B), the dispersant containing an organic compound having a carboxyl group and a polymer dispersant. This document also describes that additives such as binder resins (hydrophilic polymers such as polyvinyl alcohol and polyethylene glycol) may be added.

[0007] Japanese Patent Laid-Open Publication No. 2017-149942 (Patent Document 2) discloses an ink composition for printing or marking on a substrate, which contains silver nanoparticles, a dispersant having a carboxyl group or a salt thereof, and an aqueous solvent, and contains, in terms of solid content, 1 to 30 parts by mass of a water-soluble or water-dispersible polymer having film-forming ability per 100 parts by mass of silver nanoparticles.

[0008] JP 2018-153965 A (Patent Document 3) discloses an image-formed product having a substrate and a metallic gloss layer formed on the substrate, the metallic gloss layer including metal nanoparticles, a polymeric dispersant adsorbed to the surfaces of the metal nanoparticles, and a binder resin, the polymeric dispersant being a compound having an acid value of 1 to 80, and the binder resin being a resin having an SP value of 23.0 to 26.0. This document discloses that the binder resin is polyvinyl alcohol having a degree of saponification of 72 to 85.

[0009] Japanese Patent Laid-Open Publication No. 2018-145319 (Patent Document 4) discloses an ink containing water, a water-soluble organic solvent having a boiling point of 250° C. or less, a glittering pigment, and first resin particles containing a vinyl polymer, and second resin particles. This document describes a silver colloid particle dispersion as the glittering pigment.

[0010] Japanese Patent Application Laid-Open No. 2019-116522 (Patent Document 5) discloses an ink containing silver particles having a particle diameter Dav90 of 45 nm or less, a polyol, a silicone surfactant, and a resin. This document describes that the ink contains a water-soluble resin or a water-dispersible resin.

[0011] Japanese Patent Laid-Open Publication No. 2017-2219 (Patent Document 6) discloses a composition liquid for forming a silver mirror film layer, which is made by dissolving a polymeric dispersant in an alcohol solvent, dispersing at least one silver compound selected from silver oxide and silver carbonate in an alcohol solution, and irradiating the alcohol solution with ultrasound to obtain a dispersion solution of silver nanoparticles. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] JP 2009-227736 A [Patent Document 2] JP 2017-149942 A [Patent Document 3] JP 2018-153965 A [Patent Document 4] JP 2018-145319 A [Patent Document 5] JP 2019-116522 A [Patent Document 6] JP 2017-2219 A Summary of the Invention [Problem to be solved by the invention]

[0013] However, the inks using metal nanoparticles disclosed in Patent Documents 1 to 6 did not have sufficient silver gloss. Furthermore, in the inks, if the amount of resin such as binder is increased, metallic gloss (silver gloss) cannot be obtained, so in order to obtain high metallic gloss, it was necessary to reduce the amount of resin as much as possible. If the amount of resin is reduced, adhesion to the substrate and abrasion resistance decrease, so it was necessary to use a topcoat layer and an undercoat layer in combination. In other words, since there is a trade-off between metallic gloss and adhesion, it was difficult to achieve both properties in a simple manner.

[0014] Accordingly, an object of the present invention is to provide an ink composition having excellent metallic gloss, such as silver gloss, and uses thereof. [Means for solving the problem]

[0015] As a result of intensive research into achieving the above-mentioned object, the present inventors discovered that metallic luster, such as silver luster, can be improved by combining composite nanoparticles of a metal (including silver) and a protective colloid, a polyvinyl acetal resin, and a solvent, and thus completed the present invention.

[0016] That is, the ink composition of the present invention includes a composite nanoparticle (A) of a metal containing silver and a protective colloid, a resin component (B) containing a polyvinyl acetal resin, and a solvent (C). The polyvinyl acetal resin may be a polyvinyl butyral resin. The resin component (B) may further include a second resin. The second resin may be at least one selected from the group consisting of a (meth)acrylic resin, an alkyd resin, an epoxy resin, and a cellulose resin. The mass ratio of the polyvinyl acetal resin to the second resin may be the former / the latter=99 / 1 to 5 / 95. The solvent (C) may include at least one selected from the group consisting of an alkylene glycol monoalkyl ether and a dialkylene glycol monoalkyl ether. The ratio of the resin component (B) may be 3 to 150 parts by mass with respect to 100 parts by mass of the metal containing silver of the composite nanoparticle (A). The composite nanoparticles (A) are particles in which a protective colloid is attached or coordinated to the surface of silver-containing metal nanoparticles, the metal nanoparticles having an average particle size of 1 to 100 nm, and the protective colloid may contain a polymer dispersant having a carboxyl group or a salt thereof.

[0017] The present invention also includes a method for producing a metallic gloss film, the method including a coating step of coating the ink composition onto a substrate, and a drying step of drying a coating film formed from the ink composition to obtain a metallic gloss film.

[0018] The present invention also includes a metallic gloss film containing (A) composite nanoparticles of a metal including silver and a protective colloid, and (B) a resin component including a polyvinyl acetal resin. Effect of the Invention

[0019] In the present invention, the composite nanoparticles of a metal containing silver and a protective colloid, a polyvinyl acetal resin, and a solvent are combined, so that the metallic luster (particularly the silver luster) can be improved. Furthermore, by unevenly distributing the metal containing silver, the resin component can be increased while maintaining the metallic luster, so that the metallic luster can be achieved simultaneously with the adhesion and abrasion resistance. In detail, since a metallic luster film can be formed with high adhesion on the object to be decorated without forming a topcoat layer or a primer layer, the adhesion can be improved by a simple method, and the abrasion resistance can also be improved. Furthermore, since a dense layer can be formed on the film surface with the nanoparticles containing silver, the light shielding property (non-transmittance) is also high, and the metallic luster (mirror surface) can be improved. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 shows a transmission electron microscope (TEM) image of a cross section of the silver gloss film obtained in Example 7. [Diagram 2] FIG. 2 is an enlarged TEM image of FIG. [Diagram 3] FIG. 3 shows a TEM image of a cross section of the silver gloss film obtained in Comparative Example 1. [Figure 4] FIG. 4 is an enlarged image of the surface area of ​​the TEM image in FIG. [Diagram 5] FIG. 5 is an enlarged image of the vicinity of the interface with the substrate in the TEM image of FIG. [Figure 6] FIG. 6 is an enlarged image of the center of the film thickness in the TEM image of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] [Ink composition] The mechanism by which the ink (or ink composition) of the present invention, which contains a polyvinyl acetal-based resin (particularly a polyvinyl butyral-based resin) as a resin component, exhibits a high level of metallic luster, particularly a silver luster (mirror finish), can be presumed to be as follows.

[0022] First, when the resin component contains only polyvinyl acetal resin, it can be assumed that the molecular structure of the polyvinyl acetal resin has an effect. That is, the polyvinyl acetal resin has a hydrophobic group (acetal group such as butyral group, acetyl group) and a hydrophilic group (hydroxyl group) in the molecular chain. When the resin component is only polyvinyl acetal resin, the composite nanoparticles are unevenly distributed in either the hydrophobic group or the hydrophilic group, so that the molecular chain of the polyvinyl acetal resin has a part containing relatively many composite nanoparticles and a part containing few composite nanoparticles. That is, a structure similar to a phase separation structure of a dense phase and a sparse phase of composite nanoparticles is generated on the molecular chain of the polyvinyl acetal resin. As a result, it can be assumed that the phase containing relatively many composite nanoparticles (highly shielding phase) plays a role of shielding (not transmitting) light, and a high level of metallic luster is expressed.

[0023] On the other hand, when the resin component contains a polyvinyl acetal resin as the first resin and a second resin, it can be assumed that the phase separation structure between the resins is influential. That is, when a polyvinyl acetal resin such as a polyvinyl butyral resin is combined with a second resin such as a (meth)acrylic resin, an alkyd resin, or an epoxy resin, the first resin and the second resin undergo phase separation, and the composite nanoparticles are unevenly distributed in one of the phases. Compared to phase separation on the molecular chain of a polyvinyl acetal resin alone, in phase separation by two types of resins, the size of each phase containing a relatively large amount of composite nanoparticles becomes larger. Therefore, compared to when a polyvinyl acetal resin is used alone, even if the amount of resin relative to metals including silver is increased, a light shielding effect (non-transmittance) can be obtained, and a high level of metallic luster can be obtained. Therefore, when a first resin and a second resin are combined, a large amount of resin can be blended, and adhesion and abrasion resistance can be further improved.

[0024] In contrast, the reason why the conventional ink compositions described in Patent Documents 1 to 6 cannot exhibit high metallic luster is presumably because the binder component is a single component and the silver particles are uniformly distributed. Furthermore, in conventional ink compositions, when the proportion of the resin component is small (when the amount of the resin component relative to the metal containing silver is about 10% by mass or less), the gloss is high but the adhesion and abrasion resistance are low, and an overcoat layer and an undercoat layer are often required. On the other hand, when the proportion of the resin component is large (when the amount of the resin component relative to the metal containing silver is about 10% by mass or more), the adhesion and abrasion resistance are improved but the gloss is reduced. Therefore, in conventional metallic luster inks, the amount of resin relative to the metal containing silver needs to be kept small, and the amount of the resin component relative to the metal containing silver is at most about 10% by mass, and it is not possible to improve the adhesion and abrasion resistance with a simple structure.

[0025] (A) Composite nanoparticles The ink composition (metallic ink composition) of the present invention contains composite nanoparticles (A) of a metal including silver and a protective colloid.

[0026] In the composite nanoparticles (A), the composite form of the silver-containing metal (silver-containing metal) and the protective colloid is not particularly limited, and may be a composite attached or coordinated to the surface of the silver-containing metal nanoparticles, or a composite covering the surface of the silver-containing metal nanoparticles. Since the silver-containing metal nanoparticles have high coordination with the protective colloid (or dispersant), the protective colloid may be coordinated to the surface of the silver-containing metal nanoparticles to form a composite covering the silver-containing metal nanoparticles. When the silver-containing metal nanoparticles are composited with the protective colloid, the dispersion stability of the silver-containing metal nanoparticles can be improved, and the affinity with the resin component can be easily adjusted, forming a phase separation structure.

[0027] (Silver-containing metal nanoparticles) The silver-containing metal nanoparticles are nanometer-sized. The number average particle size (number average primary particle size) of the silver-containing metal nanoparticles is, for example, 1 to 100 nm (e.g., 2 to 80 nm), preferably 3 to 70 nm (e.g., 4 to 50 nm), and more preferably 5 to 40 nm (particularly 10 to 30 nm).

[0028] The silver-containing metal nanoparticles have the above average particle size and show a wide particle size distribution in the range of 200 nm or less, but may contain almost no coarse particles exceeding 200 nm. Therefore, the maximum primary particle size of the silver-containing metal nanoparticles is, for example, 200 nm or less, preferably 150 nm or less, and more preferably 100 nm or less.

[0029] In the silver-containing metal nanoparticles, the proportion of particles having a primary particle diameter of 100 nm or more is, by mass, for example, 10 mass% or less (e.g., 0 to 8 mass%), preferably 5 mass% or less (e.g., 0.01 to 3 mass%), and more preferably 1 mass% or less (e.g., 0.02 to 0.5 mass%).

[0030] In the present application, the particle size and particle size distribution of the silver-containing metal nanoparticles can be measured using a transmission electron microscope, and the average particle size is shown as the average value of any 10 particles.

[0031] (Metals containing silver) The metal containing silver (silver-containing metal) may be silver alone or an alloy of silver and other metals. The other metals are not particularly limited as long as they can be alloyed with silver, and examples thereof include Cr, Mo, W, Ni, Pd, Pt, Cu, Au, Zn, In, Sn, and Pb. These other metals can be used alone or in combination of two or more. Among these other metals, Cu is preferred.

[0032] The proportion of silver in the silver-containing metal may be 50% by mass or more, for example, 90% by mass or more, preferably 95% by mass or more, further preferably 97% by mass or more, more preferably 99% by mass or more, and most preferably 100% by mass (silver alone). If the proportion of silver is too low, there is a risk of the metallic gloss being reduced.

[0033] When the silver-containing metal is a combination of silver and another metal (particularly copper), the ratio of the other metal is, for example, 0.01 to 10 parts by mass, preferably 0.03 to 5 parts by mass, and more preferably 0.05 to 3 parts by mass, per 100 parts by mass of silver.

[0034] (Protective colloid) The protective colloid may be a dispersant, and is often a non-volatile dispersant. In particular, the protective colloid preferably contains a polymer dispersant having a carboxyl group or a derivative group. In this application, the carboxyl group also includes a carboxyl group in the form of an acid anhydride group.

[0035] The polymer dispersant (or polymer-type dispersant) may be any dispersant that has at least a carboxyl group and is capable of dispersing silver-containing metal nanoparticles, and may be an amphiphilic polymer dispersant (or oligomer-type dispersant).

[0036] Examples of the polymer dispersant include those that are generally used for dispersing colorants in the fields of paints and inks, etc. Representative polymer dispersants (amphiphilic polymer dispersants) include water-soluble or water-dispersible resins that contain a hydrophilic unit (or hydrophilic block) formed from a hydrophilic monomer.

[0037] Examples of the hydrophilic monomer include addition polymerizable monomers such as carboxyl group-containing monomers (unsaturated polyvalent carboxylic acids such as (meth)acrylic acid, maleic acid, maleic anhydride, or the like, or their acid anhydrides), monomers having a sulfo group (styrene sulfonic acid, etc.), and hydroxyl group-containing monomers (hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, vinylphenol, etc.); and condensation polymerizable monomers such as ethylene oxide. The condensation polymerizable monomers may form a hydrophilic unit (or block) by reacting with active hydrogen such as a hydroxyl group (e.g., the hydroxyl group). The hydrophilic monomers may form a hydrophilic unit (or block) alone or in combination of two or more kinds. Preferred hydrophilic monomers are (meth)acrylic acid, maleic acid, maleic anhydride, and ethylene oxide.

[0038] The polymer dispersant may have at least a carboxyl group, and may have a functional group of the hydrophilic monomer, such as an acid group (sulfo group) or a hydroxyl group. These functional groups may be introduced into the polymer dispersant alone or in combination of two or more kinds.

[0039] The polymer dispersant may contain at least a hydrophilic unit (or hydrophilic block), may be a homopolymer or copolymer of a hydrophilic monomer (e.g., polyacrylic acid or a salt thereof, etc.), or may be a copolymer of a hydrophilic monomer and a hydrophobic monomer. Examples of hydrophobic monomers (nonionic monomers) include (meth)acrylic acid esters [(meth)acrylic acid C such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate]. 1-20(Meth)acrylic monomers such as alkyl, (meth)acrylic acid cycloalkyl such as (meth)acrylic acid cyclohexyl, (meth)acrylic acid aryl such as (meth)acrylic acid phenyl, (meth)acrylic acid benzyl, (meth)acrylic acid 2-phenylethyl, and the like; styrene monomers such as styrene, α-methylstyrene, vinyltoluene, and the like; α-C 2-20 Olefin monomers such as olefins (ethylene, propylene, 1-butene, isobutylene, 1-hexene, 1-octene, 1-dodecene, etc.); addition polymerizable monomers such as vinyl carboxylate ester monomers such as vinyl acetate and vinyl butyrate; C monomers such as propylene oxide 3-6 Examples of the hydrophobic monomer include condensation polymerizable monomers such as alkylene oxides. The hydrophobic monomer may be used alone or in combination of two or more kinds to form the hydrophobic unit.

[0040] The polymer dispersant of a copolymer (e.g., a copolymer of a hydrophilic monomer and a hydrophobic monomer) may be a random copolymer, an alternating copolymer, a block copolymer (e.g., a copolymer composed of a hydrophilic block composed of a hydrophilic monomer and a hydrophobic block composed of a hydrophobic monomer), a comb copolymer (or a comb graft copolymer), etc. The structure of the block copolymer is not particularly limited, and may be a diblock structure, a triblock structure (ABA type, BAB type), etc. In addition, in the comb copolymer, the main chain may be formed of the hydrophilic block or the hydrophobic block, or may be formed of a hydrophilic block and a hydrophobic block. A block copolymer of a hydrophilic block and a hydrophobic block can also improve metallic gloss.

[0041] As described above, the hydrophilic unit can also be formed of a hydrophilic block (polyalkylene oxide such as polyethylene oxide, etc.). The hydrophilic block (polyalkylene oxide, etc.) and the hydrophobic block (polyolefin block, etc.) may be bonded via a linking group such as an ester bond, an amide bond, an ether bond, or a urethane bond. These bonds may be formed, for example, by modifying the hydrophobic block (polyolefin, etc.) with a modifying agent [unsaturated carboxylic acid or its anhydride (maleic anhydride, etc.), lactam or aminocarboxylic acid, hydroxylamine, diamine, etc.], and then introducing the hydrophilic block. In addition, a comb copolymer (a comb copolymer whose main chain is composed of a hydrophobic block) may be formed by reacting (or bonding) a polymer obtained from a monomer having a hydrophilic group such as a hydroxyl group or a carboxyl group (such as the hydroxyalkyl (meth)acrylate) with the condensation-based hydrophilic monomer (such as ethylene oxide).

[0042] Furthermore, the balance between hydrophilicity and hydrophobicity may be adjusted by using a hydrophilic nonionic monomer as a copolymerization component. Examples of such components include monomers or oligomers having an ethyleneoxy unit, such as 2-(2-methoxyethoxy)ethyl (meth)acrylate and polyethylene glycol mono(meth)acrylate (e.g., number average molecular weight 200 to 1,000). The balance between hydrophilicity and hydrophobicity may be adjusted by modifying (e.g., esterifying) a hydrophilic group (e.g., a carboxyl group).

[0043] In a polymer dispersant having a carboxyl group, the carboxyl group may be a salt or an acid anhydride group. For example, at least a portion of the carboxyl group may form a salt (such as a salt with an amine or a metal salt). However, a polymer dispersant in which an acid group such as a carboxyl group does not form a salt [i.e., a polymer dispersant having a free carboxyl group] can be preferably used.

[0044] The acid value of the polymer dispersant having a carboxyl group may be, for example, 1 mgKOH / g or more (e.g., 2 to 100 mgKOH / g), preferably 3 mgKOH / g or more (e.g., 4 to 90 mgKOH / g), more preferably 5 mgKOH / g or more (e.g., 6 to 80 mgKOH / g), more preferably 7 mgKOH / g or more (e.g., 8 to 50 mgKOH / g), and is usually 3 to 30 mgKOH / g (particularly 5 to 20 mgKOH / g). Note that in such a polymer dispersant, the amine value may be 0 (or almost 0).

[0045] In the polymer dispersant, the position of the functional group is not particularly limited, and may be located on the main chain, the side chain, or both the main chain and the side chain. Such a functional group may be, for example, a functional group derived from a hydrophilic monomer or a hydrophilic unit (for example, a functional group introduced by copolymerization of (meth)acrylic acid, maleic anhydride, ethylene oxide, etc.).

[0046] The polymer dispersing agents having a carboxyl group may be used alone or in combination of two or more kinds.

[0047] As the polymer dispersant, a polymer dispersant (high molecular weight pigment dispersant) described in JP-A-2004-207558 or the like may be used. The polymer dispersant may be synthesized or a commercially available product may be used. Specific examples of commercially available polymer dispersants (or dispersants composed of at least an amphiphilic dispersant) include the Solsperse series (manufactured by Avecia Co., Ltd.) such as Solsperse 13240, Solsperse 13940, Solsperse 32550, Solsperse 31845, Solsperse 24000, Solsperse 26000, Solsperse 27000, Solsperse 28000, and Solsperse 41090; Disperbyk 160, Disperbyk 161, Disperbyk 162, and Disperbyk 163; 2. Disperbic series such as Disperbic 163, Disperbic 164, Disperbic 166, Disperbic 170, Disperbic 180, Disperbic 182, Disperbic 184, Disperbic 190, Disperbic 191, Disperbic 192, Disperbic 193, Disperbic 194, Disperbic 2001, Disperbic 2015, Disperbic 2050 [manufactured by BYK-Chemie Co., Ltd.]; EFKA -46, EFKA-47, EFKA-48, EFKA-49, EFKA-1501, EFKA-1502, EFKA-4540, EFKA-4550, Polymer 100, Polymer 120, Polymer 150, Polymer 400, Polymer 401, Polymer 402, Polymer 403, Polymer 450, Polymer 451, Polymer 452, Polymer 453 [manufactured by EFKA Chemical Co., Ltd.]; Ajisper PB711, Ajisper PAl11, Ajisper PB811, Ajisper PB821, Ajisper Examples of such compounds include the Ajispar series (manufactured by Ajinomoto Co., Ltd.), such as Spar PW911; the Floren series (manufactured by Kyoeisha Chemical Co., Ltd.), such as Floren DOPA-158, Floren DOPA-22, Floren DOPA-17, Floren TG-700, Floren TG-720W, Floren-730W, Floren-740W, and Floren-745W; and the Joncryl series (manufactured by Johnson Polymer Co., Ltd.), such as Joncryl 678, Joncryl 679, and Joncryl 62.Representative polymer dispersants include Disperbyk 190, Disperbyk 194, Disperbyk 2015, etc.

[0048] The number average molecular weight of the polymer dispersant, as measured by gel permeation chromatography (GPC), is, in terms of polystyrene, for example, 1,500 to 100,000, preferably 2,000 to 80,000 (e.g., 2,000 to 60,000), more preferably 3,000 to 50,000 (e.g., 5,000 to 30,000), and still more preferably 7,000 to 20,000.

[0049] The polymer dispersant having a carboxyl group may be a polymer dispersant having no hydroxyl group.

[0050] The ratio of the protective colloid is, for example, 0.1 to 100 parts by mass (particularly, 1 to 50 parts by mass) relative to 100 parts by mass of the silver-containing metal. The ratio of the polymer dispersant having a carboxyl group can be selected from the range of, for example, about 0.1 to 60 parts by mass (e.g., 1 to 50 parts by mass) relative to 100 parts by mass of the silver-containing metal, and is usually 2 to 40 parts by mass (e.g., 2.5 to 30 parts by mass), more preferably 3 to 25 parts by mass (particularly, 5 to 20 parts by mass).

[0051] In the present application, the proportion of the protective colloid in the composite nanoparticle (A) can be measured by a conventional method, for example, thermal analysis (for example, simultaneous thermogravimetry / differential thermal analysis, etc.).

[0052] The protective colloid may contain other dispersants, if necessary, which may be inorganic compounds, but are usually organic compounds. Examples of other dispersants include alkanols (C such as hexanol, octanol, decanol, dodecanol, and octadecanol). 6-20 Alkane monools), aldehydes (caprylaldehyde, laurylaldehyde, palmitaldehyde, etc.) 6-20Aliphatic aldehydes), aliphatic hydroxycarboxylic acids, higher fatty acids or salts thereof, sulfonic acids (alkanesulfonic acids, arenesulfonic acids such as benzenesulfonic acid and toluenesulfonic acid, etc.) may be used alone or in combination of two or more of these other dispersants.

[0053] The ratio of the other dispersant is, for example, 0.1 to 100 parts by mass, preferably 0.5 to 50 parts by mass, and more preferably 1 to 30 parts by mass, relative to 100 parts by mass of the polymer dispersant.

[0054] The method for producing the composite nanoparticles is not particularly limited, and can be prepared by a conventional method, for example, when the silver-containing metal is a simple silver, the silver compound corresponding to the silver nanoparticles can be reduced in a solvent in the presence of a protective colloid and a reducing agent.Specific examples of the production method include the methods described in JP-A-2010-80442 and JP-A-2010-229544.

[0055] (B) Resin component The ink composition of the present disclosure contains a resin component containing a polyvinyl acetal resin as a first resin. The resin component (B) may contain only the first resin, or may contain the first resin and the second resin.

[0056] (B1) First resin The polyvinyl acetal resin, which is the first resin, is obtained by reacting (acetalization reaction) polyvinyl alcohol, which is obtained by saponifying polyvinyl acetate, with an aldehyde (particularly, n-butylaldehyde). In the acetalization reaction, polyvinyl alcohol cannot be completely acetalized (particularly butyralized), so hydroxyl groups remain, and a small amount of acetyl groups remain during saponification, so the polyvinyl acetal resin has acetal groups, hydroxyl groups, and acetyl groups in its constituent units.

[0057] That is, the polyvinyl acetal resin of the present invention contains, as constituent units, a vinyl acetal unit represented by the following formula (1), a vinyl alcohol unit represented by the following formula (2), and a vinyl ester unit represented by the following formula (3).

[0058] [ka]

[0059] (wherein R is a hydrogen atom or a hydrocarbon group).

[0060] In the formula (1), the hydrocarbon group represented by R includes an alkyl group, a cycloalkyl group, and an aryl group. Examples of the alkyl group include linear or branched C alkyl groups such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a n-butyl group, a t-butyl group, a hexyl group, a 2-ethyl-butyl group, an octyl group, a 2-ethylhexyl group, and a nonyl group. 1-10 Examples of the cycloalkyl group include C 111, 112, 113, 114, 115, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127, 128, 129, 130, 131, 132, 133, 13 5-10 Examples of the aryl group include C aryl groups such as phenyl groups. 6-10 As R, these hydrocarbon groups and hydrogen atoms can be used alone or in combination of two or more.

[0061] Of these, R is preferably a hydrogen atom or an alkyl group, and a linear or branched C 1-5 Alkyl groups are more preferred, and linear C 2-4 An alkyl group is more preferable, and a propyl group is most preferable. That is, the polyvinyl acetal resin is preferably a polyvinyl butyral resin (butyral resin).

[0062] The polyvinyl acetal resin may further contain other structural units in addition to the structural units represented by the formulas (1) to (3). The other structural units may be units derived from copolymerizable monomers having a radical polymerizable group.

[0063] Examples of copolymerizable monomers include C olefins such as vinyl propionate, vinyl butyrate, vinyl pivalate, and vinyl caproate. 3-8 Alkanoic acid-vinyl esters; C such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, and n-butyl vinyl ether 1-6 Alkyl vinyl ethers; α-C such as ethylene, propylene, 1-butene, isobutene, and 1-hexene 2-6 Olefins; (meth)acrylic acid and its salts; (meth)acrylic acids such as methyl (meth)acrylate, ethyl (meth)acrylate, and propyl (meth)acrylate. 1-6 Examples of the copolymerizable monomer include alkyl esters, (meth)acrylamides, and unsaturated sulfonic acids such as ethylene sulfonic acid and allyl sulfonic acid. These copolymerizable monomers can be used alone or in combination.

[0064] The polyvinyl acetal resin may be a polyvinyl acetal resin that has been modified or altered by a conventional method.

[0065] The proportion of the unit represented by the formula (1) in the polyvinyl acetal resin (acetalization degree) is about 5 to 95 mol% (e.g., 10 to 90 mol%), and may be, for example, 20 to 90 mol%, preferably 30 to 85 mol%, depending on the application, and may be 50 mol% or more (e.g., 50 to 90 mol%), preferably 60 mol% or more (e.g., 60 to 85 mol%), and more preferably 70 mol% or more (e.g., 70 to 80 mol%). The acetalization degree may be, for example, 9 to 98 mass%, preferably 25 to 95 mass%, and more preferably 35 to 90 mass%, and is 55 mass% or more (e.g., 55 to 95 mass%), preferably 65 mass% or more (e.g., 65 to 90 mass%), and more preferably 70 mass% or more (e.g., 70 to 80 mass%). If the degree of acetalization is too low, the metallic gloss may decrease, whereas if it is too high, the preparation of the polyvinyl acetal resin may become difficult.

[0066] The proportion of the units represented by the formula (2) (units having a hydroxyl group) in the polyvinyl acetal resin may be 10 to 50 mol % (for example, 15 to 40 mol %), preferably 20 to 35 mol %, and more preferably 23 to 27 mol %. The proportion of the units represented by the formula (2) in the polyvinyl acetal resin may be 5 to 40 mass % (for example, 12 to 30 mass %), preferably 15 to 25 mass %, and more preferably 18 to 23 mass %. If the proportion of the units represented by the formula (2) is too low, when the polyvinyl acetal resin is used alone as a resin component, there is a risk of a decrease in metallic gloss, and conversely, if the proportion is too high, the same applies.

[0067] The proportion of the unit represented by the formula (3) (unit having an acetyl group) in the polyvinyl acetal resin is, for example, 15 mol% or less, preferably 10 mol% or less, and more preferably 5 mol% or less. The proportion of the unit represented by the formula (3) in the polyvinyl acetal resin is, for example, 20 mass% or less, preferably 10 mass% or less, and more preferably 5 mass% or less. If the proportion of the unit represented by the formula (3) is too high, there is a risk of the metallic gloss being reduced.

[0068] The total proportion of the structural units represented by the formulas (1) to (3) in the polyvinyl acetal resin is, for example, 80 mol % or more, preferably 90 mol % or more, further preferably 95 mol % or more, and even more preferably 100 mol %.

[0069] The proportion of the copolymerizable monomer in the polyvinyl acetal resin is, for example, 20 mol % or less, preferably 10 mol % or less, and more preferably 5 mol % or less.

[0070] In the present application, the degree of acetalization of the polyvinyl acetal resin and the proportion of each unit can be measured by a conventional method, for example, titration, IR elemental analysis, NMR method, etc. In the case of a butyral resin, the degree of acetalization can be measured by a method conforming to JIS K 6728 "Testing method for polyvinyl butyral".

[0071] The weight average molecular weight of the polyvinyl acetal resin (particularly, butyral resin) is, for example, 3,000 to 300,000, preferably 5,000 to 100,000, further preferably 7,000 to 70,000, more preferably 10,000 to 40,000, and most preferably 12,000 to 20,000. If the molecular weight is too small, the metallic gloss and mechanical properties of the metallic gloss film may decrease, whereas if the molecular weight is too high, the film formability may decrease.

[0072] In the present application, the weight average molecular weight of the polyvinyl acetal resin is a value calculated based on the molecular weight of standard polystyrene from a chromatogram measured by gel permeation chromatography (GPC) in accordance with the method described in JIS K 0124-2011.

[0073] The glass transition temperature of the polyvinyl acetal resin (particularly, butyral resin) can be selected from the range of about 50 to 130° C., and is, for example, 60 to 125° C., preferably 70 to 120° C., further preferably 80 to 115° C., more preferably 90 to 115° C., and most preferably 100 to 110° C. If the glass transition temperature is too low, the metallic luster and mechanical properties of the metallic luster film may decrease, and conversely, if it is too high, the film formability may decrease.

[0074] In the present application, the glass transition temperature of the polyvinyl acetal resin can be measured by using a differential scanning calorimeter (DSC).

[0075] The viscosity of a 10 mass % solution of a polyvinyl acetal resin (particularly, a butyral resin) (solvent: toluene / ethanol (mass ratio) = 50 / 50) when measured at a temperature of 20°C using a rotational viscosity type (BM type) can be selected from a range of about 2 to 20,000 mPa·s (particularly, 10 to 10,000 mPa·s) and, depending on the application, may be, for example, 5 to 1,000 mPa·s (e.g., 10 to 500 mPa·s), preferably 20 to 400 mPa·s (e.g., 25 to 300 mPa·s), more preferably 50 to 250 mPa·s (e.g., 70 to 200 mPa·s), and may be, for example, 3 to 150 mPa·s (e.g., 5 to 100 mPa·s), preferably 10 to 50 mPa·s (particularly, 10 to 30 mPa·s). If the viscosity is too low, the metallic luster and mechanical properties of the metallic luster film may decrease, whereas if the viscosity is too high, the film-forming properties may decrease.

[0076] (B2) Second resin The second resin (B2) is not particularly limited as long as it is a resin that can be phase-separated from the first resin, but is preferably at least one selected from the group consisting of (meth)acrylic resins, alkyd resins, epoxy resins, and cellulose resins.

[0077] ((Meth)acrylic resin) The (meth)acrylic resin is not particularly limited, and may be, for example, a homopolymer or copolymer of a (meth)acrylic monomer, a (meth)acrylic polyol, or a modified (meth)acrylic resin.

[0078] Examples of the (meth)acrylic monomer include (meth)acrylic acid; (meth)acrylic acid C such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate. 1-20Alkyl; cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate; aryl (meth)acrylates such as phenyl (meth)acrylate; aralkyl (meth)acrylates such as benzyl (meth)acrylate and 2-phenylethyl (meth)acrylate; hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate 1-4 These (meth)acrylic monomers can be used alone or in combination of two or more. Among these, (meth)acrylic acid C such as methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate are preferred. 1-4 Alkyl; hydroxyethyl (meth)acrylate, etc. 2-3 Alkyl (meth)acrylates are preferred.

[0079] The (meth)acrylic resin may be a homopolymer of these monomers, but a copolymer is preferred. The copolymer may be a copolymer of two or more of the (meth)acrylic monomers, or a copolymer of the (meth)acrylic monomer and a copolymerizable monomer. Examples of the copolymerizable monomer include styrene monomers such as styrene, α-methylstyrene, and vinyltoluene; α-C 2-20 Examples of the copolymerizable monomer include olefin monomers such as olefins (ethylene, propylene, 1-butene, isobutylene, 1-hexene, 1-octene, 1-dodecene, etc.); and addition polymerizable monomers such as vinyl carboxylate monomers such as vinyl acetate and vinyl butyrate. These copolymerizable monomers can be used alone or in combination of two or more. Among these, styrene monomers such as styrene are preferred.

[0080] When the (meth)acrylic resin is a copolymer of a (meth)acrylic monomer and a styrene monomer (particularly, a copolymer of a methacrylic monomer and a styrene monomer), the molar ratio of the (meth)acrylic monomer to the styrene monomer (former / latter) is 95 / 5 to 5 / 95, preferably 90 / 10 to 10 / 90, further preferably 80 / 20 to 20 / 80, and further preferably 70 / 30 to 30 / 70.

[0081] The (meth)acrylic polyol is not particularly limited as long as it is a (meth)acrylic polymer having two or more hydroxyl groups in the molecule. For example, a hydroxy C monomer for the (meth)acrylic resin may be used. 2-3 It may be a (meth)acrylic resin containing an alkyl (meth)acrylate.

[0082] Examples of modified (meth)acrylic resins include polyester-modified (meth)acrylic resins such as polyester (meth)acrylate, polyurethane-modified (meth)acrylic resins such as urethane (meth)acrylate, epoxy-modified (meth)acrylic resins such as epoxy (meth)acrylate, silicone-modified (meth)acrylic resins such as silicone (meth)acrylate, etc. These modified (meth)acrylic resins can be used alone or in combination of two or more.

[0083] These (meth)acrylic resins can be used alone or in combination of two or more. Among these, (meth)acrylic resins having hydroxyl groups are preferred, and (meth)acrylic resins having hydroxyl groups and styrene units (e.g., methyl (meth)acrylate-styrene copolymers, etc.) are particularly preferred, because they have high affinity with silver-containing metal nanoparticles (especially composite nanoparticles (A)) and are easily cured with a curing agent depending on the application. The position of the hydroxyl group is not particularly limited, and may be in the main chain, may be in the side chain, or may be located in the main chain and the side chain.

[0084] The hydroxyl value of the (meth)acrylic resin may be, for example, 1 mgKOH / g or more (e.g., 2 to 400 mgKOH / g), preferably 3 mgKOH / g or more (e.g., 4 to 300 mgKOH / g), more preferably 5 mgKOH / g or more (e.g., 6 to 200 mgKOH / g), more preferably 7 mgKOH / g or more (e.g., 8 to 150 mgKOH / g), and is usually 10 to 150 mgKOH / g (particularly 50 to 100 mgKOH / g). If the hydroxyl value is too small, there is a risk that the metallic gloss and the mechanical properties of the metallic gloss film will decrease, and conversely, if the hydroxyl value is too high, there is a risk that the metallic gloss will decrease.

[0085] In the present application, the hydroxyl value of the (meth)acrylic resin can be measured by a conventional method, for example, neutralization titration method.

[0086] The weight average molecular weight of the (meth)acrylic resin is, for example, 1,000 to 100,000, preferably 2,000 to 80,000 (e.g., 3,000 to 50,000), further preferably 5,000 to 30,000 (e.g., 10,000 to 20,000), and even more preferably 12,000 to 16,000. If the molecular weight is too small, the mechanical properties of the metallic gloss film may be reduced, and conversely, if it is too high, the film formability may be reduced.

[0087] In the present application, the weight average molecular weight of the (meth)acrylic resin is a value calculated from a chromatogram measured by gel permeation chromatography (GPC) based on the molecular weight of standard polystyrene.

[0088] The glass transition temperature of the (meth)acrylic resin is, for example, 0 to 120° C., preferably 40 to 110° C., more preferably 50 to 100° C., and most preferably 60 to 90° C. If the glass transition temperature is too low, the mechanical properties of the metallic gloss film may be reduced, whereas if it is too high, the film formability may be reduced.

[0089] In the present application, the glass transition temperature of the (meth)acrylic resin can be measured using a differential scanning calorimeter.

[0090] The (meth)acrylic resin may be a (meth)acrylic resin that does not have a carboxyl group or a salt thereof.

[0091] The proportion of the (meth)acrylic resin is, for example, 1 to 50 parts by mass, preferably 3 to 40 parts by mass, more preferably 5 to 30 parts by mass, more preferably 10 to 25 parts by mass, and most preferably 15 to 20 parts by mass, relative to 100 parts by mass of the silver-containing metal of the composite nanoparticle (A) in terms of solid content. If the proportion of the (meth)acrylic resin is too low, there is a risk of reduced adhesion and abrasion resistance, and if it is too high, there is a risk of reduced metallic gloss.

[0092] (Alkyd resin) The alkyd resin is a conventional alkyd resin used in the paint field and the like, and may be, for example, a short oil alkyd resin, a long oil alkyd resin, a modified alkyd resin, an isocyanate-cured alkyd resin, an epoxy ester resin (epoxy-modified alkyd resin), an alkyd polyol, an oil-free alkyd resin, or the like.

[0093] A specific alkyd resin may be, for example, a synthetic resin defined in JIS K 5500 "Paint Terminology", that is, a synthetic resin obtained by condensation polymerization of a polybasic acid and an oil component with a polyol (polyhydric alcohol).

[0094] Examples of polybasic acids include aromatic dibasic acids such as phthalic acid, phthalic anhydride, isophthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, and 5-sodium sulfoisophthalic acid; alicyclic dibasic acids such as tetrahydrophthalic acid, tetrahydrophthalic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride, and 1,4-cyclohexanedicarboxylic acid; aliphatic dibasic acids such as succinic acid, succinic anhydride, alkenylsuccinic acid, alkenylsuccinic anhydride, fumaric acid, maleic acid, maleic anhydride, itaconic acid, adipic acid, sebacic acid, azelaic acid, himic acid, and himic acid anhydride; and trifunctional or higher polybasic acids such as trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic anhydride, methylcyclohexene tricarboxylic acid, methylcyclohexene tricarboxylic acid anhydride, and benzophenone tetracarboxylic acid.

[0095] These polybasic acids can be used alone or in combination of two or more. Among these, aromatic dicarboxylic acids such as isophthalic acid and terephthalic acid are widely used.

[0096] The oil component (oil and fat component) includes fatty oils (oils and fats) and / or fatty acids.

[0097] Examples of fatty oils include vegetable oils such as cottonseed oil, linseed oil, tung oil, castor oil, dehydrated castor oil, safflower oil, soybean oil, rice oil, corn oil, sesame oil, sunflower oil, rice sugar oil, asami oil, rapeseed oil, peanut oil, coconut oil, palm oil, kapok oil, almond oil, olive oil, tall oil, and oyster oil; animal oils such as beef tallow, lard, mutton tallow, goat tallow, horse tallow, chicken tallow, and turkey tallow; fish oils such as herring oil, flounder oil, cod oil, sole oil, halibut oil, carp oil, trout oil, and catfish oil; and hydrogenated oils thereof. These oils and fats can be used alone or in combination of two or more.

[0098] Fatty acids include straight-chain or branched-chain saturated C acids such as caprylic acid, capric acid, pelargonic acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, arachidic acid, and behenic acid. 8-24Fatty acids; linear or branched unsaturated C such as myristoleic acid, palmitoleic acid, petroselinic acid, oleic acid, vaccenic acid, linoleic acid, linolenic acid, eleostearic acid, gadolinic acid, arachidonic acid, and erucic acid. 8-24 Fatty acids and the like. These fatty acids may have a substituent such as a hydroxyl group. Examples of fatty acids having a hydroxyl group include ricinoleic acid, savinic acid, and dioxystearic acid, which are the main components of castor oil. The fatty acid may be a fatty acid obtained by saponification or the like from the fatty oil, such as a hygienic fatty acid obtained from dehydrated castor oil, or a fatty acid obtained from linseed oil, tung oil, dehydrated castor oil, soybean oil, safflower oil, etc. (e.g., linseed oil fatty acid, tung oil fatty acid, dehydrated castor oil fatty acid, soybean oil fatty acid, safflower oil fatty acid, etc.). These fatty acids can be used alone or in combination of two or more.

[0099] Among these oil components, vegetable oils such as linseed oil, tung oil, dehydrated castor oil, soybean oil, and safflower oil; fatty acids derived from these vegetable oils; and saturated fatty acids such as stearic acid. 10-22 Fatty acids; unsaturated C such as oleic acid, linoleic acid, linolenic acid, stearic acid, eleostearic acid or ricinoleic acid 10-22 Fatty acids are preferred.

[0100] Examples of polyols include diols such as ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, neopentyl glycol, diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, tetramethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, hydrogenated bisphenol A, and 2-butyl-2-ethyl-1,3-propanediol; triols such as glycerin, trimethylolpropane, and trimethylolethane; polyols having tetrafunctional or more functional groups such as pentaerythritol, diglycerin, ditrimethylolpropane, ditrimethylolethane, tris(2-hydroxyethyl)isocyanurate, and dipentaerythritol; and polyhydric alcohols that have been used in alkyd resins.

[0101] These polyols can be used alone or in combination of two or more kinds. Among these, aliphatic polyols such as glycerin, trimethylolpropane, pentaerythritol, and dipentaerythritol are widely used.

[0102] In addition to the oil component and the polyol, the alkyd resin may further contain a monobasic acid such as benzoic acid, pt-butylbenzoic acid, abietic acid, hydrogenated abietic acid, and the like.

[0103] The hydroxyl value of the alkyd resin is, for example, 5 to 500 mgKOH / g, preferably 10 to 300 mgKOH / g, further preferably 20 to 200 mgKOH / g, and further preferably 50 to 150 mgKOH / g. If the hydroxyl value is too small, the metallic gloss and the mechanical properties of the metallic gloss film may decrease, whereas if the hydroxyl value is too high, the metallic gloss may decrease.

[0104] In the present application, the hydroxyl value of the alkyd resin can be measured in accordance with ISO 4629(2).

[0105] The acid value of the alkyd resin is, for example, 0.5 to 30 mgKOH / g, preferably 1 to 20 mgKOH / g, further preferably 2 to 15 mgKOH / g, and further preferably 3 to 8 mgKOH / g. If the acid value is too small, the metallic gloss may decrease, whereas if it is too high, the metallic gloss and the mechanical properties of the metallic gloss film may decrease.

[0106] In the present application, the acid value of the alkyd resin can be measured in accordance with JIS K 5601-1-2.

[0107] The weight average molecular weight of the alkyd resin is, for example, 500 to 30,000, preferably 1,000 to 20,000, and more preferably 2,000 to 10,000. If the molecular weight is too small, the mechanical properties of the metallic gloss film may be reduced, and conversely, if it is too high, the film formability may be reduced.

[0108] In the present application, the weight average molecular weight of the alkyd resin is a value calculated from a chromatogram measured by gel permeation chromatography (GPC) based on the molecular weight of standard polystyrene.

[0109] (Epoxy resin) The epoxy resin may be a compound having two or more epoxy groups in the molecule. The epoxy resin includes glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, glycidyl ester type epoxy resin, etc. Among these, glycidyl ether type epoxy resin is widely used.

[0110] Examples of the glycidyl ether type epoxy resin include bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, cresol novolac type epoxy resin, phenol novolac type epoxy resin, bisphenol A novolac type epoxy resin, alcohol ether type epoxy resin, tetrabromobisphenol A type epoxy resin, and naphthalene type epoxy resin.

[0111] These epoxy resins can be used alone or in combination of two or more kinds. Among these, bisphenol type epoxy resins such as bisphenol A type epoxy resins are preferred.

[0112] The epoxy equivalent of the epoxy resin is, for example, 100 to 5,000 g / eq, preferably 300 to 3,000 g / eq, more preferably 500 to 1,500 g / eq, and even more preferably 700 to 1,000 g / eq. If the epoxy equivalent of the epoxy resin is too small, the mechanical properties of the metallic gloss film may be reduced, and conversely, if it is too high, the metallic gloss may be reduced.

[0113] In the present application, the epoxy equivalent is defined as "the mass of an epoxy resin containing one equivalent of an epoxy group" and can be measured in accordance with JIS K 7236.

[0114] The number average molecular weight of the epoxy resin is, for example, 5,000 to 100,000, preferably 7,000 to 70,000, further preferably 10,000 to 40,000, and even more preferably 12,000 to 20,000. If the molecular weight is too small, the mechanical properties of the metallic gloss film may be reduced, and conversely, if it is too high, the film formability may be reduced.

[0115] In the present application, the number average molecular weight of the epoxy resin can be measured in accordance with the method described in JIS K 0124-2011, and is a value calculated based on the molecular weight of standard polystyrene from a chromatogram measured by gel permeation chromatography (GPC).

[0116] The softening point of the epoxy resin, measured by a method in accordance with JIS K 7234, is 30 to 150° C., preferably 50 to 130° C., further preferably 70 to 120° C., and even more preferably 90 to 100° C. If the softening point is too low, the mechanical properties of the metallic gloss film may be reduced, whereas if the softening point is too high, the film formability may be reduced.

[0117] In this application, the softening point of an epoxy resin is the temperature measured based on the ring and ball method of JIS K 7234, in which a sample is filled into a specified ring, supported horizontally in a water bath or glycerin bath, a specified ball is placed in the center of the sample, and the bath temperature is raised at a rate of 5°C per minute when the sample encasing the ball comes into contact with the bottom plate of the ring stand.

[0118] (Cellulosic resin) The cellulose-based resin is not particularly limited, but may be, for example, a cellulose derivative such as a cellulose ester.

[0119] Examples of cellulose derivatives include cellulose esters, cellulose ethers, and cellulose ether esters. Examples of cellulose esters include inorganic cellulose esters such as nitrocellulose, cellulose sulfate, and cellulose phosphate; organic cellulose esters such as cellulose acetate, cellulose propionate, cellulose butyrate, cellulose acetate propionate, cellulose acetate butyrate, and cellulose acetate propionate butyrate. Examples of cellulose ethers include cellulose alkyl ethers such as methylcellulose and ethylcellulose; carboxyalkyl celluloses such as carboxymethylcellulose; and hydroxyalkyl celluloses such as hydroxymethylcellulose, hydroxyethylcellulose, and hydroxypropylmethylcellulose. Examples of cellulose ether esters include cellulose ether esters such as carboxymethylcellulose acetate, carboxymethylcellulose propionate, and carboxymethylcellulose butyrate.

[0120] These cellulose derivatives can be used alone or in combination. Among these, cellulose organic acid esters are preferred, cellulose acylate is more preferred, and cellulose C is more preferred. 2―4 Acylate is more preferred, and cellulose acetate C 3-4The cellulose organic acid ester may be produced by reacting cellulose with an organic acid and / or an acid anhydride, and in particular, may be produced by converting cellulose into a triester with an organic acid and / or an acid anhydride, followed by hydrolysis.

[0121] The degree of ester substitution of the cellulose acylate is, for example, 30 to 70% by mass, preferably 35 to 60% by mass, more preferably 40 to 55% by mass, and even more preferably 45 to 50% by mass. 3-4 The degree of acetyl substitution of the acylate is, for example, 0.5 to 30% by mass, preferably 1 to 10% by mass. 3-4 The degree of acyl substitution is, for example, 15 to 60% by mass, and preferably 30 to 50% by mass.

[0122] The number average molecular weight of the cellulose-based resin is, for example, 1,000 to 100,000, preferably 5,000 to 50,000, further preferably 10,000 to 30,000, and even more preferably 15,000 to 25,000. If the molecular weight is too small, the mechanical properties of the metallic gloss film may be reduced, and conversely, if it is too high, the film formability may be reduced.

[0123] In the present application, the number average molecular weight of the cellulose-based resin is a value calculated from a chromatogram measured by gel permeation chromatography (GPC) based on the molecular weight of standard polystyrene.

[0124] The glass transition temperature of the cellulose-based resin is, for example, 80 to 180° C., preferably 100 to 160° C., more preferably 120 to 150° C., and most preferably 130 to 140° C. If the glass transition temperature is too low, the mechanical properties of the metallic gloss film may be reduced, whereas if it is too high, the film formability may be reduced.

[0125] In the present application, the glass transition temperature of the cellulose-based resin can be measured using a differential scanning calorimeter.

[0126] (Characteristics and proportions of second resin) Among the second resins, (meth)acrylic resins, alkyd resins and cellulose resins are preferred, with alkyd resins being particularly preferred, in view of excellent metallic gloss.

[0127] The mass ratio of the first resin (polyvinyl acetal resin) to the second resin can be selected from the range of about the former / latter = 100 / 0 to 5 / 95 (particularly 99 / 1 to 5 / 95), for example, 95 / 5 to 5 / 95 (for example, 90 / 10 to 10 / 90), preferably 80 / 20 to 20 / 80, more preferably 70 / 30 to 30 / 70, more preferably 60 / 40 to 40 / 60. If the ratio of the second resin is too high, there is a risk of the metallic gloss being reduced. In applications where metallic gloss is important, the first resin / second resin = 99 / 1 to 50 / 50, preferably 98 / 2 to 60 / 40, more preferably 95 / 5 to 70 / 30, more preferably 93 / 7 to 80 / 20, and most preferably 92 / 8 to 85 / 15.

[0128] (Ratio of resin component (B)) The ratio of the resin component (B) can be selected from the range of about 3 to 150 parts by mass (for example, 5 to 100 parts by mass) relative to 100 parts by mass of the silver-containing metal of the composite nanoparticle (A), for example, 5 to 120 parts by mass (for example, 10 to 80 parts by mass), preferably 7 to 100 parts by mass (for example, 7 to 80 parts by mass), more preferably 8 to 60 parts by mass (for example, 15 to 50 parts by mass), more preferably 10 to 50 parts by mass (for example, 20 to 40 parts by mass), and most preferably 10 to 30 parts by mass. In applications where metallic gloss is important, the ratio of the resin component (B) is, for example, 6 to 50 parts by mass, preferably 7 to 30 parts by mass, more preferably 8 to 20 parts by mass, and more preferably 9 to 15 parts by mass relative to 100 parts by mass of the silver-containing metal of the composite nanoparticle (A). If the ratio of the resin component (B) is too small, there is a risk that the adhesion and abrasion resistance will decrease, and if it is too large, there is a risk that the metallic gloss will decrease.

[0129] (C) Solvent The ink composition of the present invention further contains a solvent (C). By blending the solvent (C) with the resin component (B), the film-forming property can be improved, and when the resin component (B) contains a second resin, phase separation due to spinodal decomposition can be promoted.

[0130] The solvent (C) preferably contains a polar organic solvent. Examples of the polar organic solvent include alcohols (C such as methanol, ethanol, propanol, and isopropanol). 1-4 alkanols, etc.), polyhydric alcohols (alkanediols such as ethylene glycol and propylene glycol, alkanetriols such as glycerin and trimethylolpropane, alkanetetraols such as pentaerythritol, etc.), amides (acylamides such as formamide and acetamide, mono- or di-C alkyl amides such as N-methylformamide, N-methylacetamide, N,N-dimethylformamide, and N,N-dimethylacetamide, etc.) 1-4 acylamides, etc.), pyrrolidones (2-pyrrolidone, 3-pyrrolidone, N-methyl-2-pyrrolidone, N-methyl-3-pyrrolidone, etc.), ketones (acetone, diacetone alcohol, methyl ethyl ketone, isophorone, etc.), ethers (dioxane, tetrahydrofuran, etc.), organic carboxylic acids (acetic acid, etc.), esters (methyl acetate, ethyl acetate, isopropyl acetate, butyl acetate, amyl acetate, etc.), alkylene glycol monoalkyl ethers (methyl cellosolve, ethyl cellosolve, propyl cellosolve, butyl cellosolve, propylene glycol methyl ether, 3-methoxy-3-methyl-1-butanol, etc.) 2-6 Alkylene glycol mono C 1-4 alkyl ethers, etc.), dialkylene glycol monoalkyl ethers (di-C such as methyl carbitol, ethyl carbitol, propyl carbitol, and butyl carbitol) 2-6 Alkylene glycol mono C 1-4 Alkyl ethers, etc.), cellosolve acetates (ethyl cellosolve acetate, etc.) 1-4 Alkyl cellosolve acetates), carbitol acetates (methyl carbitol acetate, butyl carbitol acetate, etc.) 1-4 alkyl carbitol acetate, dimethyl sulfoxide, etc. These polar organic solvents can be used alone or in combination of two or more kinds.

[0131] The proportion of the polar organic solvent in the solvent may be 50% by mass or more, preferably 70% by mass or more, further preferably 80% by mass or more, and even more preferably 90% by mass or more, and may be 100% by mass.

[0132] The solvent (C) may further contain a non-polar solvent in addition to the polar solvent. Examples of the non-polar solvent include aliphatic hydrocarbons such as hexane, octane, and decane, and alicyclic hydrocarbons such as cyclohexane and tetralin. The ratio of the non-polar organic solvent may be 50 parts by mass or less (for example, about 0.1 to 50 parts by mass) relative to 100 parts by mass of the polar organic solvent, preferably 30 parts by mass or less, and more preferably 10 parts by mass or less.

[0133] Among these solvents, it is preferable to include at least one selected from alcohols, esters, alkylene glycol monoalkyl ethers, and dialkylene glycol monoalkyl ethers, it is more preferable to include at least one selected from esters, alkylene glycol monoalkyl ethers, and dialkylene glycol monoalkyl ethers, and it is even more preferable to include at least one selected from alkylene glycol monoalkyl ethers and dialkylene glycol monoalkyl ethers. 2-6 Alkylene glycol mono C 1-6 Alkyl ethers and diC 2-6 Alkylene glycol mono C 1-6 More preferably, one or more selected from alkyl ethers are C 2-5 Alkylene glycol mono C 1-4 Alkyl ethers and diC 2-5 Alkylene glycol mono C 1-4 The dialkylene glycol monoalkyl ether may be a polar solvent derived from a dispersion medium for dispersing silver colloid particles as a raw material.

[0134] The ratio of the solvent (C) is, for example, 50 to 1,000 parts by mass, preferably 100 to 500 parts by mass, further preferably 200 to 450 parts by mass, more preferably 250 to 400 parts by mass, and most preferably 300 to 350 parts by mass, relative to 100 parts by mass of the silver-containing metal of the composite nanoparticles (A). If the ratio of the solvent is too small, the film-forming properties may decrease, and if a second resin is included, it may be difficult to form a phase-separated structure. Conversely, if the ratio is too large, the productivity and film-forming properties may decrease.

[0135] (D) Hardener The ink composition of the present invention may further contain a curing agent (D) in addition to the composite nanoparticles (A), the resin component (B) and the solvent (C). The curing agent (D) may be a conventional curing agent, such as an isocyanate-based curing agent, an amine-based curing agent, an acid anhydride-based curing agent, or an imidazole-based curing agent. Among these, an isocyanate-based curing agent is preferred, and a polyisocyanate is particularly preferred. An isocyanate-based curing agent such as a polyisocyanate is particularly effective when the first resin and the second resin have a functional group (particularly a hydroxyl group).

[0136] Examples of polyisocyanates include aliphatic polyisocyanates [diisocyanates such as propylene diisocyanate, trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), trimethylhexamethylene diisocyanate (TMDI), and lysine diisocyanate (LDI); triisocyanates such as 1,6,11-undecane triisocyanate, methyl octane, and 1,3,6-hexamethylene triisocyanate, and polyisocyanates], alicyclic polyisocyanates [cyclohexane 1,4-diisocyanate, isophorone diisocyanate (IPDI), hydrogenated xylylene diisocyanate, and polyisocyanates], and polyisocyanates such as cyclohexane 1,4-diisocyanate, isophorone diisocyanate (IPDI), hydrogenated xylylene diisocyanate, and polyisocyanates]. diisocyanates such as bis(isocyanatophenyl)methane and hydrogenated bis(isocyanatophenyl)methane; tri- or polyisocyanates such as bicycloheptane triisocyanate, etc.], aromatic polyisocyanates [diisocyanates such as phenylene diisocyanate, tolylene diisocyanate (TDI), xylylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), naphthalene diisocyanate (NDI), bis(isocyanatophenyl)methane (MDI), toluidine diisocyanate (TODI), 1,3-bis(isocyanatophenyl)propane, etc.; tri- or polyisocyanates], etc.

[0137] The polyisocyanate may be a derivative such as a polymer (dimer, trimer, tetramer, etc.), an adduct, or a modified product (biuret modified product, allophanate modified product, urea modified product, etc.), or a urethane oligomer having a plurality of isocyanate groups. Examples of modified products or derivatives of polyisocyanate include an adduct of a polyisocyanate (an aliphatic polyisocyanate such as hexamethylene diisocyanate) and a polyhydric alcohol (trimethylolpropane, pentaerythritol, etc.), a biuret of the polyisocyanate, and a polymer of the polyisocyanate (for example, an aliphatic polyisocyanate) (for example, a polyisocyanate having an isocyanurate ring such as a trimer of hexamethylene diisocyanate).

[0138] These polyisocyanates can be used alone or in combination of two or more. Among these polyisocyanates, aliphatic polyisocyanates or their derivatives (e.g., HDI or its trimer, etc.), aromatic polyisocyanates (TDI, MDI, etc.), etc. are widely used.

[0139] The proportion of the curing agent (D) is, for example, 10 to 200 parts by mass, preferably 20 to 150 parts by mass, and more preferably 25 to 100 parts by mass, relative to 100 parts by mass of the resin component (B).

[0140] (E) Other metal nanoparticles The ink composition of the present invention may further contain other metal nanoparticles (E) in addition to the composite nanoparticles (A), the resin component (B) and the solvent (C). The other metal nanoparticles (E) may be, for example, a metal of Group 8 of the periodic table (iron, nickel, cobalt, ruthenium, rhodium, palladium, rhenium, iridium, platinum, etc.), a metal of Group 1B of the periodic table (copper, gold, etc.), a metal of Group 3B of the periodic table (aluminum, gallium, indium, etc.) and a metal of Group 4B of the periodic table (germanium, tin, lead, etc.). The metal (metal atom) is often a metal that has high coordination with the protective colloid, such as a metal of Group 8 of the periodic table or a metal of Group 1B of the periodic table. The ratio of the other metal nanoparticles (E) is 100 parts by mass or less, preferably 50 parts by mass or less, more preferably 10 parts by mass or less, relative to 100 parts by mass of the silver-containing metal of the composite nanoparticles (A).

[0141] (F) Other ingredients The ink composition of the present invention may further contain, as other components (F), conventional additives such as plasticizers (or film-forming assistants), gloss-imparting agents, metal corrosion inhibitors (rust inhibitors), stabilizers (antioxidants, ultraviolet absorbers, light stabilizers, etc.), surfactants (anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, particularly anionic surfactants and / or nonionic surfactants), dispersion stabilizers, thickeners or viscosity adjusters, moisturizers, thixotropic agents, leveling agents, penetrants, defoamers, pH adjusters, chelating agents, surface tension adjusters, colorants (dyes and pigments, etc.), hue improvers, dye fixing agents, bactericides, fungicides, preservatives, oxygen absorbers, etc., within the scope of not impairing the effects of the present invention. The surfactants may be acetylene glycol-based surfactants, polysiloxane-based surfactants, fluorine-based surfactants, etc. These additives may be used alone or in combination of two or more. The proportion of the other component (F) is 50 parts by mass or less, preferably 30 parts by mass or less, and more preferably 10 parts by mass or less, per 100 parts by mass of the silver-containing metal of the composite nanoparticle (A).

[0142] [Method of preparing ink composition] The ink composition of the present invention can be prepared by mixing the composite nanoparticles (A), the resin component (B) and the solvent (C) in a conventional manner. A conventional stirring device can be used as the mixing method, for example, a stirring and degassing device can be used. The composite nanoparticles (A) may be mixed with the resin component (B) and the alkylene glycol monoalkyl ether as the solvent (C) in the form of a dispersion in which the composite nanoparticles (A) are dispersed in the dialkylene glycol monoalkyl ether as the solvent (C).

[0143] [Method of manufacturing metallic gloss film] The metallic gloss film is obtained through a coating step in which the ink composition is applied onto an object to be decorated (substrate) to form a coating film, and a drying step in which the coating film is dried to obtain the metallic gloss film.

[0144] In the coating step, the type of substrate is not particularly limited, and a resin substrate (film, etc.), a metal substrate, a glass substrate, a ceramic substrate, paper, etc. can be used depending on the application.

[0145] The coating method is not particularly limited, and a conventional coating method such as a flow coating method, a dispenser coating method, a spin coating method, a spray coating method, a screen printing method, a flexographic printing method, a casting method, a bar coating method, a curtain coating method, a roll coating method, a gravure coating method, a dipping method, a slit method, a photolithography method, an inkjet method, or an offset printing method can be used.

[0146] The average thickness (dry thickness) of the coating film is, for example, 0.05 to 100 μm, preferably 0.1 to 30 μm, further preferably 0.5 to 10 μm, and even more preferably 1 to 5 μm.

[0147] In the present invention, metallic luster, adhesion and abrasion resistance can be achieved simultaneously without forming an undercoat layer or a topcoat layer, but an undercoat layer and / or a topcoat layer may be used in combination depending on the application.

[0148] In the drying step, the coating film is dried to form a metallic gloss film. As a method for drying the coating film, a method of drying by heating is preferred, and a method of drying by heating in two stages, combining a preliminary heating treatment and a main heating treatment, is preferred from the viewpoint of facilitating the formation of a phase separation structure.

[0149] In the preheating treatment, the preheating temperature is, for example, 40 to 80° C., preferably 45 to 70° C., more preferably 45 to 60° C., and more preferably 45 to 55° C. The preheating time is, for example, 1 to 100 minutes, preferably 3 to 60 minutes, and more preferably 5 to 30 minutes.

[0150] In this heat treatment, the heating temperature is, for example, 60 to 150° C., preferably 65 to 120° C., more preferably 70 to 90° C., and more preferably 75 to 85° C. The heating time is, for example, 30 to 240 minutes, preferably 80 to 180 minutes, and more preferably 100 to 150 minutes.

[0151] When the resin component (B) contains a second resin, a metallic gloss film may be formed by forming phase separation due to spinodal decomposition in the drying step. When the second resin is contained, the coating film can be separated into a phase containing a large amount of silver-containing metal and a phase containing a small amount of silver-containing metal by spinodal decomposition with the evaporation of the solvent by drying the coating film.

[0152] The metallic gloss film obtained by the above method is formed on a substrate (object to be decorated), and is laminated on the substrate, and contains composite nanoparticles (A) of a metal containing silver and a protective colloid, and a resin component (B) containing a polyvinyl acetal resin. The average thickness of the metallic gloss film is, for example, 0.05 to 100 μm, preferably 0.1 to 30 μm, more preferably 0.3 to 10 μm, more preferably 0.5 to 5 μm, and most preferably 1 to 3 μm.

[0153] In particular, the metallic luster film formed on the substrate and containing the second resin may have a structure in which an interface layer, an intermediate layer, and a surface layer are laminated in this order on the substrate.

[0154] The interface layer is formed of the composite nanoparticles, and the composite nanoparticles are arranged or oriented at the interface with the substrate to form a dense thin film of metal containing silver (silver-containing metal thin film). By forming such an interface layer at the interface with the substrate, the metallic luster from the back side of a transparent substrate can be improved.

[0155] The average thickness of the interface layer is, for example, 5 to 300 nm, preferably 10 to 200 nm, further preferably 10 to 100 nm, and even more preferably 20 to 40 nm.

[0156] In the present application, the average thickness of the interface layer can be measured by observing the cross section of the silver gloss film with a transmission electron microscope (TEM), and in detail, can be measured by the method described in the examples below.

[0157] The intermediate layer has a phase-separated structure in which a first phase containing the composite nanoparticles and a first resin and a second phase containing the composite nanoparticles and a second resin are separated into phases with different contents of silver-containing metal. By having a phase-separated structure with different concentrations of silver-containing metal, it is possible to improve metallic luster even if the proportion of the resin component is increased, and it is possible to achieve both metallic luster and adhesion and abrasion resistance.

[0158] The ratio of the first phase to the second phase (area ratio in the cross section), first phase / second phase, is 90 / 10 to 10 / 90, preferably 70 / 30 to 30 / 70, further preferably 60 / 40 to 40 / 60, and further preferably 55 / 45 to 45 / 55.

[0159] In the present application, the ratio can be measured based on a transmission electron microscope (TEM) image of a cross section of the silver gloss film, and in detail, can be measured by the method described in the examples below.

[0160] The phase-separated structure may be a sea-island structure or a co-continuous structure. Of these, a sea-island structure is preferred. When the intermediate layer has a sea-island structure, the continuous phase (matrix phase) constituting the sea portion may be either a first phase or a second phase.

[0161] In the sea-island structure, the average diameter of the dispersed phase is, for example, 10 to 3,000 nm, preferably 100 to 1,000 nm, further preferably 150 to 500 nm, and even more preferably 200 to 300 nm.

[0162] The average pitch of the dispersed phase (the average value of the distance between the centers of adjacent dispersed phases) is, for example, 10 to 2,000 nm, preferably 100 to 1,000 nm, further preferably 200 to 700 nm, and further preferably 300 to 500 nm.

[0163] The observation method of the cross section of the metallic luster film is not particularly limited, and a method used in normal structural analysis can be used. The observation method includes morphological and structural observation using a transmission electron microscope (TEM), a scanning electron microscope (SEM), an electron beam microanalyzer (EPMA), a scanning probe microscope (SPM), etc.; and analysis of the constituent elements using fluorescent X-rays, energy dispersive X-ray spectroscopy (EDX), wavelength dispersive X-ray spectroscopy (WDX), electron energy-loss spectroscopy (EELS), etc. Among these, transmission electron microscope (TEM) observation is preferable because it allows observation of even the finest structures. The sample to be observed can be appropriately processed and used so as to be suitable for observation and analysis. For example, a thin sample may be prepared using a microtome or the like.

[0164] Therefore, in the present application, the structure, size and distribution state of the island structure in the cross section of the metallic gloss film can be observed and measured based on the TEM image of the cross section of the silver gloss film, and the size is the average value of 10 arbitrary points. In detail, it can be measured by the method described in the examples below. Furthermore, in the TEM image, the silver-containing metal nanoparticles are dark in color, so they can be easily confirmed, and in the intermediate layer, the aggregated part of the silver-containing metal nanoparticles is the dispersed phase.

[0165] The average thickness of the intermediate layer is, for example, 0.01 to 100 μm, preferably 0.05 to 30 μm, further preferably 0.1 to 10 μm, and even more preferably 0.2 to 1 μm.

[0166] The average thickness of the intermediate layer may be at least twice the average thickness of the surface layer, for example, 2 to 1,000 times, preferably 3 to 100 times, further preferably 3.5 to 50 times, and even more preferably 4 to 10 times.

[0167] In the present application, the average thickness of the intermediate layer can be measured by observing the cross section of the metallic gloss film with a transmission electron microscope (TEM), and is the average value of any three points.

[0168] The surface layer is formed of the composite nanoparticles, and the composite nanoparticles are arranged or oriented on the surface of the metallic gloss film to form a dense thin film (metal thin film) of silver-containing metal. In the present invention, the metallic gloss can be improved by forming such a surface layer on the surface of the metallic gloss film.

[0169] The average thickness of the surface layer is, for example, 3 to 300 nm, preferably 5 to 200 nm, further preferably 10 to 150 nm, and even more preferably 30 to 100 nm.

[0170] In the present application, the average thickness of the surface layer can be measured by observing the cross section of the silver gloss film with a transmission electron microscope (TEM), and in detail, can be measured by the method described in the examples below. EXAMPLES

[0171] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following examples, the preparation method of the ink composition and the measurement method of the evaluation test are shown below.

[0172] [Materials used] (First resin) Polyvinyl butyral resin A: "S-LEC KS-10" manufactured by Sekisui Chemical Co., Ltd., degree of acetalization 74 mol% or more, acetyl group 3 mol% or less, hydroxyl group 25 mol%, 10 mass% solution viscosity (temperature 20°C, rotational viscosity type (BM type), solvent = toluene / ethanol = 50 / 50 (mass ratio)) 10 to 30 mPa s, glass transition temperature 106°C, weight average molecular weight 17,000 Polyvinyl butyral resin B: "S-LEC SV-12" manufactured by Sekisui Chemical Co., Ltd., hydroxyl group 22 mol%, 10 mass% solution viscosity (temperature 20°C, rotational viscosity type (BM type), solvent = toluene / ethanol = 50 / 50 (mass ratio)) 70 mPa·s, glass transition temperature 76°C, weight average molecular weight 30,000 Polyvinyl butyral resin C: "S-LEC SV-16" manufactured by Sekisui Chemical Co., Ltd., hydroxyl group 22 mol %, 10 mass % solution viscosity (temperature 20°C, rotational viscosity type (BM type), solvent = toluene / ethanol = 50 / 50 (mass ratio)) 80 mPa s, glass transition temperature 80°C, weight average molecular weight 100,000.

[0173] (Second resin) Acrylic resin A: DIC Corporation "WXU-880", isocyanate-curing acrylic resin, non-volatile content 50%, hydroxyl value 10 mgKOH / g, glass transition temperature 90°C Acrylic resin B: "ARUFON UH2170" manufactured by Toagosei Co., Ltd., styrene acrylic resin, non-volatile content 98% or more, hydroxyl value 88 mg KOH / g, glass transition temperature 60°C Alkyd resin: DIC Corporation "D-128-65BA", isocyanate-cured alkyd resin, non-volatile content 65%, hydroxyl value 90 mg KOH / g, acid value 5.0 mg KOH / g Epoxy resin: Mitsubishi Chemical Corporation "jER1055", bisphenol A type epoxy resin, epoxy equivalent 850, softening point 93°C, number average molecular weight 1600 Silicone resin: Shin-Etsu Chemical Co., Ltd. "KR211", methylphenyl silicone resin Cellulose-based resin: Cellulose acetate butyrate "CAB-553-0.4" manufactured by Tomoe Engineering Co., Ltd., acetyl group 2%, butyryl group 46%, hydroxyl group 4.8%, falling ball speed 0.30 seconds, glass transition temperature 136°C, number average molecular weight 20,000.

[0174] (solvent) 3-Methoxy-3-methyl-1-butanol: manufactured by Tokyo Chemical Industry Co., Ltd., boiling point 174°C Butyl cellosolve: Fujifilm Wako Pure Chemical Industries, Ltd., boiling point 171°C Ethyl carbitol: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., boiling point 202°C.

[0175] (Polymer dispersant) Polymer dispersant A with carboxyl group: "Disperbyk 190" manufactured by BYK-Chemie, solution of high molecular weight block copolymer with pigment affinity group, solvent: water, non-volatile component 40%, acid value 10 mg KOH / g, amine value 0 Polymer dispersant B having a carboxyl group: "Disperbyk 2015" manufactured by BYK-Chemie, a solution of an acrylic copolymer having a pigment affinity group, solvent: water, non-volatile components 40%, acid value 10 mg KOH / g, amine value 0.

[0176] [Glossiness] The 20° gloss was measured using an appearance analyzer (Rhopoint IQ-S, manufactured by Konica Minolta Japan, Inc.) and ranked according to the following criteria (A, B, C, D). Note that a gloss value of 400 or more is enough to visually confirm a metallic gloss (mirror surface), so ranks A, B, and C were considered to be acceptable.

[0177] Rank A: Glossiness is 600 or more (passed) Rank B: Glossiness is between 400 and 600 (pass) Rank C: Glossiness is between 300 and 400 (pass) Rank D: Glossiness is less than 300 (failure).

[0178] [Light opacity] The visible light transmittance in the wavelength range of 380 to 780 nm was measured using an ultraviolet-visible-near infrared spectrophotometer (Shimadzu Corporation's "UV-3100PC") and an integrating sphere ISR-3100. The integral value of the transmittance relative to the integral value of the blank measurement (air) was calculated by integrating the transmittance in the wavelength range of 380 to 780 nm, and was evaluated according to the following criteria. The smaller the integral value of the transmittance relative to the blank measurement, the lower the transmittance of the film and the better it is.

[0179] ○: The integral value of the transmittance is 1.0% or less (pass) △: The integral value of the transmittance is 5.0% or less (pass) ×: The integral value of the transmittance is greater than 5.0% (failure).

[0180] [Adhesion] Cellotape (registered trademark) was applied to the cured film and then peeled off vigorously, and the film was evaluated according to the following criteria.

[0181] ○: No peeling of the film (passed) △: There is slight peeling on the surface of the film, but the substrate is not visible (passed) ×: The film peeled off (failed).

[0182] [Abrasion resistance] The cured film was subjected to a friction test using a friction and abrasion tester with dry cotton at a load of 500g and 10 reciprocations. The 20° gloss of the cured film after the friction test was measured, and the reduction rate of gloss before and after the friction test was calculated, and the abrasion resistance was evaluated according to the following criteria.

[0183] ○: Gloss reduction rate is less than 20% (pass) △: Gloss reduction rate is 20% or more and less than 50% (pass) ×: The gloss level decreased by 50% or more (failed).

[0184] [Overall Judgment] Based on the results of glossiness, light impermeability, adhesion, and abrasion resistance, a rating of superiority or inferiority was made according to the following criteria, with A, B, and C being considered pass.

[0185] A rating: Glossiness is rank A, and light impermeability, adhesion, and abrasion resistance are all ◯ Grade B: Gloss is rank A and light impermeability, adhesion, and abrasion resistance are all pass (including one △), or gloss is rank B and light impermeability, adhesion, and abrasion resistance are pass (○ or △). C rating: Glossiness is rank A and light impermeability, adhesion, and abrasion resistance are all pass (including two or more △), or glossiness is rank C and light impermeability, adhesion, and abrasion resistance are pass (○ or △). D rating: Glossiness is rank D, or any of the following is unsatisfactory: light impermeability, adhesion, or abrasion resistance.

[0186] [Cross-section observation of membrane] A sample was cut out from the obtained silver gloss film, embedded in epoxy resin, a general-purpose embedding resin, and the cut cross section was exposed with a microtome and observed with a SEM. Furthermore, in order to observe the fine structure, after exposing the cut cross section with a microtome, ultra-thin sections with a thickness of about 100 nm or less were prepared, and observed with a TEM. The size (average diameter and average pitch) of the dispersed phase was measured by the following method.

[0187] (Average thickness of surface layer and interface layer) The thickness of the layer in which the silver nanoparticles were arranged was measured in the enlarged TEM images near the surface and near the interface. The average value of the layer thicknesses measured at three random locations was taken as the average thickness.

[0188] (average diameter of dispersed phase) The major and minor axes of the dispersed phase (islands) where silver nanoparticles are aggregated were measured, and the average was taken as the diameter of the dispersed phase (islands).The average of the diameters calculated for any 10 dispersed phases (islands) was taken as the average diameter of the dispersed phase.

[0189] (average pitch of dispersed phase) The intersection of the major axis and minor axis of the dispersed phase was defined as the center of the dispersed phase, and the distance between the centers of adjacent dispersed phases was measured. The average value of the center-to-center distances measured at 10 random locations was taken as the average pitch of the dispersed phase.

[0190] (Ratio of 1st and 2nd phases) The first and second phases were binarized using the image processing software "ImageJ" (available from https: / / imagej.Nih.gov / ij / ) for the cross-sectional TEM image. The areas of the first and second phases were determined from the binarized image processing image, and the ratio of the first and second phases was calculated. In this example, the ratio was calculated without excluding the surface layer and the interface layer, so the ratio of the first phase also includes the areas of the surface layer and the interface layer.

[0191] Examples 1 to 31 and Comparative Examples 1 to 7 (Method for preparing silver nanoparticle dispersion A) 66.8 g of silver nitrate and 7.2 g of polymer dispersant A having a carboxyl group were added to 100 g of ion-exchanged water and stirred vigorously to obtain a suspension. 100 g of dimethylaminoethanol (manufactured by Wako Pure Chemical Industries, Ltd.) was gradually added to this suspension so that the water temperature did not exceed 50°C, and then the suspension was heated and stirred in a water bath at 50°C for 4 hours.

[0192] An excess amount of methanol was added to the silver nanoparticle dispersion and stirred, then the silver nanoparticles were precipitated by centrifugation, and the supernatant was removed. Methanol was added again and stirred, then the silver nanoparticles were precipitated by centrifugation, and the supernatant was removed. Diethylene glycol monobutyl ether was added to the resulting methanol solution containing the precipitate, and the mixed methanol was removed with an evaporator to obtain a silver nanoparticle (composite nanoparticle) dispersion A with a silver content of 70 mass%. When the particle size of the silver nanoparticles in this dispersion was confirmed with a transmission electron microscope (manufactured by JEOL Ltd.), the number average particle size of the primary particles was about 20 nm.

[0193] (Method for preparing silver nanoparticle dispersion B) Silver nanoparticle (composite nanoparticle) dispersion B was prepared in the same manner as silver nanoparticle dispersion A, except that polymer dispersant B having a carboxyl group was used instead of polymer dispersant A having a carboxyl group. When the particle size of the silver nanoparticles in the obtained silver nanoparticle dispersion B was confirmed with a transmission electron microscope (manufactured by JEOL Ltd.), the number average particle size of the primary particles was about 30 nm.

[0194] (Method for preparing silver / copper alloy nanoparticle dispersion) 65.58 g of silver nitrate and 7.2 g of polymeric dispersant A having a carboxyl group were added to 100 g of ion-exchanged water and vigorously stirred to obtain suspension A.

[0195] 1.40 g of copper (II) nitrate trihydrate and 2.93 g of a 1 mol / L aqueous nitric acid solution were taken and stirred in a water bath at 50°C to dissolve the copper (II) nitrate trihydrate, and aqueous solution B was obtained.

[0196] The suspension A and the aqueous solution B were mixed with stirring to obtain a mixed solution of a polymer dispersant having a carboxyl group, silver nitrate, and copper nitrate.

[0197] To this mixture, 100 g of dimethylaminoethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was gradually added so that the water temperature did not exceed 50° C., and then the mixture was heated and stirred in a water bath at 50° C. for 4 hours.

[0198] An excess amount of methanol was added to the obtained dispersion containing silver / copper alloy nanoparticles and stirred, and then the silver / copper alloy nanoparticles were precipitated by centrifugation, and the supernatant was removed. Methanol was added again and stirred, and then the silver / copper alloy nanoparticles were precipitated by centrifugation, and the supernatant was removed. Diethylene glycol monobutyl ether was added to the methanol solution containing the obtained precipitate, and the mixed methanol was removed with an evaporator, to obtain a silver / copper alloy nanoparticle (composite nanoparticle) dispersion in which the ratio of copper to 100 parts by mass of silver was 1 part by mass and the silver / copper alloy content was 70% by mass. When the particle size of the silver / copper alloy nanoparticles in this dispersion was confirmed with a transmission electron microscope (manufactured by JEOL Ltd.), the number average particle size of the primary particles was about 20 nm.

[0199] (Method of preparing metallic ink composition) The obtained metal nanoparticle dispersion, resin component, and solvent were stirred and mixed in the ratios shown in Tables 1 to 5 using a stirring and degassing device ("Mazerustar" manufactured by Kurabo Industries, Ltd.) to prepare metallic ink compositions. The amount of resin in the tables is the content converted into solid content. The metallic ink composition was applied to a glass substrate (substrate) with an applicator to a thickness of 20 μm. Thereafter, the substrate was heated on a hot plate at 50° C. for 10 minutes, and then heated on a hot plate at 80° C. for 120 minutes. The thickness of the obtained metallic gloss film (the dry thickness of the coating film) was about 2 μm.

[0200] The evaluation results of the obtained metallic gloss film are shown in Tables 1 to 5.

[0201] [Table 1]

[0202] [Table 2]

[0203] [Table 3]

[0204] [Table 4]

[0205] [Table 5]

[0206] The results of the verification of the amount and type of resin components are shown in Table 1.

[0207] In Examples 1 to 3, in which only polyvinyl butyral resin A was used as the resin component and silver nanoparticles were used as the composite nanoparticles, and the amount of resin relative to silver was varied to 10 mass%, 30 mass%, and 50 mass%, a metallic gloss film excellent in glossiness, light impermeability, adhesion, and abrasion resistance (overall judgment A) was obtained. In Example 4, in which the amount of resin was further increased to 100 mass% relative to silver, glossiness and light impermeability were slightly reduced, but were still at a practical level (overall judgment C).

[0208] In Example 5, in which the type of resin component was changed to polyvinyl butyral resin B compared to Example 2, and in Example 6, in which the type of resin component was changed to polyvinyl butyral resin C, a metallic gloss film equivalent to that of Example 2 (overall evaluation A) was obtained.

[0209] In Comparative Examples 1 to 5 in which the type of resin component was changed to a resin other than polyvinyl butyral resin in Example 2, Comparative Example 1 using acrylic resin A and Comparative Example 5 using silicone resin failed in glossiness (overall judgement: D). Moreover, Comparative Example 2 using acrylic resin B, Comparative Example 3 using alkyd resin, and Comparative Example 4 using epoxy resin had pass-level glossiness, but failed in light non-transmittance (overall judgement: D).

[0210] In addition, in Comparative Example 6, which does not contain any resin component, the glossiness and light impermeability were at an acceptable level, but the adhesion and abrasion resistance were unacceptable (overall evaluation: D).

[0211] Table 2 shows the verification results when polyvinyl butyral resin was combined with a second resin (acrylic resin A, acrylic resin B, alkyd resin, epoxy resin, cellulose-based resin) as the resin component.

[0212] Examples 7 to 9 were prepared by keeping the amount of resin relative to silver at 30% by mass, the mass ratio of polyvinyl butyral resin to second resin in the resin constant at polyvinyl butyral resin:second resin=50:50, and varying the type of polyvinyl butyral resin. As a result, in Examples 7 to 9, metallic gloss films excellent in glossiness, light non-transmittance, adhesion, and abrasion resistance (overall evaluation A) were obtained.

[0213] In Examples 10 to 13, in which the second resin was changed from that of Example 7, metallic gloss films excellent in glossiness, light impermeability, adhesion and abrasion resistance (overall rating A or B) were obtained.

[0214] In Comparative Example 7, in which acrylic resin A was combined with an epoxy resin as a combination of two types of resins not including polyvinyl butyral resin, the gloss, adhesion and abrasion resistance were at acceptable levels, but the light non-transmittance was unacceptable (overall rating: D).

[0215] Table 3 shows the verification results when the mass ratio of polyvinyl butyral resin A to the second resin (acrylic resin A) was changed while keeping the amount of resin to the silver nanoparticles equal (30 mass%) in Example 2, in which only polyvinyl butyral resin A was used as the resin component.

[0216] In the following order, the gloss level tended to decrease, although it was at the pass level (overall judgment A or B), in Example 2 (polyvinyl butyral resin A: acrylic resin A = 100:0) which did not use acrylic resin A, Example 14 (polyvinyl butyral resin A: acrylic resin A = 90:10) which contained a small amount of the second resin, Example 7 (polyvinyl butyral resin A: acrylic resin A = 50:50) which contained equal amounts of both, Example 15 (polyvinyl butyral resin A: acrylic resin A = 20:80) which had a higher ratio of the second resin than Example 7, and Example 16 (polyvinyl butyral resin A: acrylic resin A = 10:90). Furthermore, in Example 17 (polyvinyl butyral resin A: acrylic resin A = 5:95) which had a higher ratio of the second resin, the gloss level and light impermeability were further decreased, but were at a practical level (overall judgment C). In the above-mentioned Comparative Example 1 (polyvinyl butyral resin A:acrylic resin A=0:100) in which only acrylic resin A was used without polyvinyl butyral resin A, the glossiness and light impermeability were unacceptable (overall evaluation: D).

[0217] Polyvinyl butyral resin A and acrylic resin A were used as the resin components, and the mass ratio between them was equal in Example 7. Verification results obtained by varying the amount of resin relative to the silver nanoparticles are shown in Table 4. Note that the "amount of resin relative to silver nanoparticles (mass%)" is synonymous with the ratio (parts by mass) of the resin component relative to 100 parts by mass of silver nanoparticles.

[0218] All of the examples were passable (overall rating A to C), but as the amount of resin relative to the silver nanoparticles increased, the glossiness and light impermeability tended to decrease, while the adhesion and abrasion resistance tended to improve. Example 20 (10% by mass), Example 7 (30% by mass), and Example 21 (50% by mass), in which the amount of resin relative to the silver nanoparticles was 10 to 50% by mass, were overall rated A, whereas Example 19, in which the amount of resin was 7% by mass, had decreased adhesion, and Example 18, in which the amount of resin was 5% by mass, had decreased adhesion and abrasion resistance. On the other hand, in Example 22, in which the amount of resin was 100% by mass, the glossiness and light impermeability decreased, and in Example 23, in which the amount of resin was 120% by mass, the glossiness further decreased.

[0219] From the above results, it can be said that the amount of resin relative to the silver nanoparticles can be practically used in the range of 5 to 120 mass%, with the range of 7 to 100 mass% being preferred, and that the range of 10 to 50 mass% is a more suitable range for obtaining a metallic gloss film that has an excellent balance of gloss, light impermeability, adhesion, and abrasion resistance.

[0220] Table 5 shows the verification results when the protective colloid of the silver nanoparticles (composite nanoparticles) was changed, when silver / copper alloy nanoparticles were used as the composite nanoparticles, and when the solvent was changed.

[0221] First, the above-mentioned changes were made in Example 2, which used only polyvinyl butyral resin A as the resin component. In Example 24, in which silver nanoparticle dispersion 1 in the composition of Example 2 was changed to silver nanoparticle dispersion 2 with a different protective colloid, and in Example 25, in which it was changed to a silver / copper alloy nanoparticle dispersion, a metallic gloss film equivalent to that of Example 2 (overall judgment A) was obtained. In addition, in Example 26, in which the solvent in the composition of Example 2 was changed to butyl cellosolve, and in Example 27, in which it was changed to ethyl carbitol, a metallic gloss film equivalent to that of Example 2 (overall judgment A) was obtained.

[0222] Next, the above-mentioned changes were made in Example 7, which used polyvinyl butyral resin A and acrylic resin A as resin components (the mass ratio was equal). In Example 28, in which the silver nanoparticle dispersion 1 in the composition of Example 7 was changed to silver nanoparticle dispersion 2 with a different protective colloid, and in Example 29, in which the silver / copper alloy nanoparticle dispersion was changed, a metallic gloss film equivalent to that of Example 7 (overall judgment A) was obtained. In addition, in Example 30, in which the solvent in the composition of Example 7 was changed to butyl cellosolve, and in Example 31, in which the solvent was changed to ethyl carbitol, a metallic gloss film equivalent to that of Example 7 (overall judgment A) was obtained.

[0223] Cross-sectional photographs of the metallic luster film obtained in Example 7 are shown in Figures 1 and 2. Figure 2 is an enlarged TEM image of Figure 1. In Figures 1 and 2, the upper side of the TEM image is the interface layer side with the substrate, and the lower side is the surface layer side.

[0224] In the silver gloss film of Example 7, which had a high glossiness, the inside of the film (intermediate layer) was phase-separated into a region where silver nanoparticles were aggregated (dispersed phase) and a region where silver nanoparticles were less aggregated (continuous phase). That is, the silver nanoparticles had a structure in which they were unevenly distributed in the dispersed phase. Furthermore, as is clear from the enlarged image in FIG. 2, the silver nanoparticles were aligned on the surface and at the interface with the substrate to form a thin continuous layer (thin layer).

[0225] The average thicknesses of the surface layer and the interface layer in Example 7 were measured to be 58 nm and 37 nm, respectively. The average thickness of the intermediate layer was measured to be 300 nm. The average thickness of the intermediate layer was 5.2 times that of the surface layer.

[0226] Furthermore, the average diameter and average pitch of the dispersed phase (region where silver nanoparticles are aggregated) in the intermediate layer were measured, and the average diameter was 241 nm and the average pitch was 313 nm. The area ratio of the dispersed phase (first phase) to the second phase was measured, and the ratio was first phase / second phase=51 / 49.

[0227] Figures 3 to 6 show cross-sectional photographs of the metallic gloss film obtained in Comparative Example 1. As is clear from Figure 3 showing an overall image and Figures 4 to 6 showing enlarged images of the inside of the film, in the silver gloss film of Comparative Example 1, which had low gloss, silver nanoparticles were uniformly dispersed throughout the film. [Industrial Applicability]

[0228] The ink composition of the present invention can be used to improve the decorativeness of various objects (molded objects) to be decorated, and can be used, for example, for decorating interior and exterior parts of automobiles, emblems, mobile phones, notebook computers, golf club shafts, soft packaging, cosmetic containers, and the like, for painting purposes, and as an ink for inkjet printing methods.

Claims

1. An ink composition for improving the decorativeness of an object to be decorated, comprising: A method for producing a composite nanoparticle of a metal including silver and a protective colloid (A), a resin component including a polyvinyl acetal resin (B), and a solvent (C), The ink composition, wherein the protective colloid contains a polymer dispersant having a carboxyl group or a salt thereof.

2. 2. The ink composition according to claim 1, wherein the polyvinyl acetal resin is a polyvinyl butyral resin.

3. The ink composition according to claim 1 or 2, wherein the resin component (B) further comprises a second resin.

4. 4. The ink composition according to claim 3, wherein the second resin is at least one selected from the group consisting of (meth)acrylic resins, alkyd resins, epoxy resins and cellulose resins.

5. 5. The ink composition according to claim 3, wherein a mass ratio of the polyvinyl acetal resin to the second resin is the former / the latter=99 / 1 to 5 / 95.

6. The ink composition according to any one of claims 1 to 5, wherein the solvent (C) comprises at least one selected from the group consisting of alkylene glycol monoalkyl ethers and dialkylene glycol monoalkyl ethers.

7. 7. The ink composition according to claim 1, wherein the ratio of the resin component (B) is 3 to 150 parts by mass per 100 parts by mass of the metal containing silver of the composite nanoparticles (A).

8. The ink composition according to any one of claims 1 to 7, wherein the composite nanoparticles (A) are particles in which a protective colloid is attached to or coordinated to the surface of silver-containing metal nanoparticles, and the metal nanoparticles have an average particle size of 1 to 100 nm.

9. A method for producing a metallic gloss film, comprising: a coating step of coating a substrate with the ink composition according to any one of claims 1 to 8; and a drying step of drying a coating film formed with the ink composition to obtain a metallic gloss film.

10. A metallic gloss film for improving the decorativeness of a decorated object, comprising: The present invention comprises a composite nanoparticle (A) of a metal including silver and a protective colloid, and a resin component (B) including a polyvinyl acetal resin, and The metallic luster film, wherein the protective colloid contains a polymer dispersant having a carboxyl group or a salt thereof.

Citation Information

Patent Citations

  • Stable metal colloid and usage of the same

    JP2006035205A

  • Ink composition for inkjet printing

    JP2009227736A

  • Ink composition

    JP2011052046A

  • Method for producing composition liquid for forming silver mirror film layer, and method for forming silver mirror film layer

    JP2017002219A

  • Ink composition and image formation method therewith

    JP2017149942A